Oculomotor response to linear acceleration as induced by counter-rotation in supine subjects - Cheung, B; Money, K; Eizenman, M (Aviation, space, and environmental medicine, 1998)
Horizontal nystagmus occurs in response to sinusoidal linear accelerations directed along an upright subject's Y (interaural) axis, and is proposed to be mediated by an utricular otolith mechanism. The otolith organs, composed of the utricles and saccules, provide a unique set of signals for any linear acceleration in 3-dimensional space. A supine subject under alternate changing directions of linear acceleration as induced by counter-rotation will receive alternate stimulation along the Y as well as the Z (dorsoventral) axis. We hypothesized that alternate horizontal and vertical nystagmus would be elicited as a result of the changing direction of linear acceleration. A group of eight subjects in the supine position were exposed to counter-rotation at 0.16, 0.25, and 0.33 Hz. Vertical and horizontal eye movements were recorded simultaneously using the El-Mar eye and head tracking system. Horizontal nystagmus was observed in all supine subjects. The direction of the slow phase of nystagmus changed with directional changes in linear acceleration. Reversals in the direction of eye movements lagged behind the reversals in the direction of the acceleration. However, only two subjects exhibited alternating horizontal and vertical nystagmus as a result of changing axis of linear acceleration, from "along the Y axis" to "along the Z axis." We propose that the nystagmus induced in the supine subject was provoked by linear acceleration and largely an otolith-mediated reflex. The lack of vertical response could be due to the relative paucity of vestibular afferents information along the dorsoventral axis.